PENINGKATAN KESADARAN MASYARAKAT NASABAH BANK MUAMALAT CABANG BATAM TERHADAP PENCEGAHAN UANG PALSU - Sahputri, Rini Dewi; Laili , Nur Isra; Putra , Additiya Dian Eko (PUAN INDONESIA, 2025)
This community service program aims to raise public awareness regarding the circulation of counterfeit money and provide understanding about the procedures for opening accounts in Islamic banking. The activity was carried out through direct interaction with customers at PT Bank Muamalat Indonesia, Batam Branch. The implementation included assistance in completing account opening forms, document verification, and education on how to identify genuine banknotes. The method used was direct communication (face-to-face), allowing for practical and easily comprehensible delivery of the material. The results showed a significant improvement in customers’ understanding of the characteristics of authentic Indonesian banknotes, along with growing interest in utilizing digital and cashless financial services. It is expected that this initiative contributes to efforts in preventing the circulation of counterfeit money and enhances financial literacy, particularly within the context of Islamic banking.